Konflik dalam Keluarga Modern dan Akar Permasalahannya - Maudy Fathia; M. Ibrahim Aziz; Ais Surasa (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
The family is a group of people who join together as one because of blood ties and kinship. The more members of his family the more opinions will be raised. Families are vessels for shelter, protection, spilling love and sharing all sorrows as well. In the digital age, many families are contaminated by constant change and circumstances. That’s when each opinion of the family members will clash, even tear each other down. It cannot be avoided by anyone because anyone is obliged to resolve it. This research is library research, which is a study that uses literature by studying books, books, and other sources of information that have relevance to the scope of the discussion. The results show that conflicts in modern families occur due to several things, namely childcare patterns, family economy, and unequal domestic burdens. The lack of communication space between family members is also a cause of conflict in the family.